Implementation Of Public Relations Management Development At Boarding Schools In The Smart Society 5.0 Era - Aji Wahyudin; Ainun Rohman; Ulfa Fauziah (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
This study aims to describe the implementation and development of public relations management at the Zainul Hasan Genggong Islamic Boarding School in the era of smart society 5.0. The research method used is a case study. Which is located at Zainul Hasan Genggong Pajarakan Islamic Boarding School, Probolinggo. This study uses descriptive qualitative research, with its research methods, namely interviews, documentation, and observation. The results of the study show that public relations management at Zainul Hasan Genggong Islamic Boarding School is very influential. with a good management system in the form of planning, implementation, and evaluation. All programs can run as intended. The Public Relations Management of Zainul Hasan Genggong Islamic Boarding School has been kept up to date, which has also utilized information and communication technology, including the Web, Instagram, Twitter, Facebook, YouTube, and even TikTok. So that the management of public relations is very effective both in the implementation and the results obtained. Although several challenges and obstacles must be faced, all of them can be overcome with a good public relations management system to achieve a better image.  Keywords: Public Relations, Islamic Boarding Schools